Dripper clogging: emphasis on the problem and how to minimize impact - Alvarenga Almeida, Isabela; José de Sousa Pereira, Diego; de Oliveira Costa, Jéfferson; Alberto Quiloango-Chimarro, Carlos; Duarte Coelho, Rubens (Revista Brasileira de Engenharia de Biossistemas, 2022)
Irrigation is a useful tool to achieve a better productivity and quality foods, which contributes to a higher efficient use of agriculture land. Drip irrigation is characterized by higher application efficiency, providing an efficient control of the irrigation depth required. Moreover, it has advantages such as lower evaporation loss and higher crop yields when associated with fertigation. However, dripper clogging is pointed out by several authors as the main limiting factor for a rapid adoption of drip irrigation on a larger scale. Emitter clogging susceptibility depends basically on five parameters: water quality, filtration system, fertilizer quality, labyrinth architectural layout and maintenance procedures. The adoption of chemical treatments helps to control biological agents and precipitates, making it possible to minimize the risk of clogging. This paper aims to understand how drip clogging process occurs, providing scientific arguments and support on the development of a standardized test pattern, making progress in order to identify commercial emitters that are less susceptible to clogging under field conditions.